PHAMBILI WITH THE SPIRIT OF SELF-REFLECTION - Kometsi, Kgamadi (PINS-Psychology in Society, 2026)
The qualitative methods stream of the recent PsySSA conference (15-18 August 2000) attracted some of the most interesting papers and presentations of the event. This was particularly important, given the heated verbal exchanges of the AGM which threatened to distract attention away from the academic aspect of the conference. Of course there were a lot of titles on the programme of the qualitative methods stream that promised to be good, but which only made rt as far as the programme itself, and never got presented, for whatever reason. One of the qualities of the presentations in this stream, that maintained interest in those who attended, seemed to be the diversity of the topics covered Some of the presenters located their papers generally within the broad ambit of the critical psychology approach, whereas others could be identified as actively using critical psychology principles given that they contained some ·evaluation of the theories and practices of psychology, in terms of how they maintain an unjust and unsatisfying status quo" (Fox & Prilleltensky, 1997:3). It is against this understanding that critical psychology, as an approach, will be used as a frame for this commentary.